Midwives in Egypt, Mesopotamia, and Ancient Israel: An Intersectional Investigation - Yee, Gale A. (Biblical theology bulletin, 2022)
Although we have some artifacts of birth equipment from archaeology, this study will argue that the knowledge we have about midwives in ancient Israel, Egypt, and Mesopotamia primarily comes to us from the hegemonic domain of ideologies, myths, ideas, and symbols. Texts about the goddesses of birth relate something about the social roles and practices of midwives in the human sphere. The decline or complete absence of the goddess in these mythic or religious texts may offer clues about gendered, raced, and classed relations among humans in their respective ancient societies. Moreover, midwives will continue to play symbolic and ideological roles in the textual arena of today’s modern world.